Analysis of the Implementation of the Hiwar Method in Learning Arabic Language at the Tahfizh Islamic Boarding School of the Surro Man Roa Wakaf Foundation - Harun Ar Rasyid; Nurainun Hasibuan (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
This research aims to find out and explain the application of the war method carried out by teachers in learning Arabic at the Surro Man Roa Waqf Foundation Islamic Boarding School. This research uses a type of field research which is qualitative with a descriptive approach. The data collection techniques used were observation and interviews. Then the data was analyzed using the Miles and Huberman model and validated using the Membercheck technique. The results of this research show that the application of the hiwar method at the Surro Man Roa Waqf Foundation Islamic Boarding School is going well with the main role of the teacher in guiding this method and also the students' active participation in following it. Thus, the war method at the Surro Man Roa Waqf Foundation Islamic Boarding School has succeeded in illustrating the success of the approach. learning that does not only focus on Arabic but also on forming the character and thinking skills of students. The active role of the ustadz as a facilitator, including providing motivation, guiding, overcoming uncertainty, and creating a dynamic learning atmosphere, is the key to success.